Structure and Magnetic Properties of Monodisperse Fe3+-doped CeO2 Nanospheres - Phokha, Sumalin; Pinitsoontorn, Supree; Maensiri, Santi (Nano-Micro Letters, 2013)
This work reports the study concerning the structure and magnetic properties of undoped CeO2 and Fe-doped CeO2 (Ce1−xFe x O2, 0.01 ≤ x ≤ 0.07) nanospheres with diameters of 100∼200 nm prepared by hydrothermal method using polyvinylpyrrolidone (PVP) as surfactant. The prepared samples were studied by using X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), X-ray absorption near-edge structure (XANES), and vibrating sample magnetometry (VSM). The XRD results showed that Fe-doped CeO2 was single-phased with a cubic structure, and with Fe3+ successfully substituting in Ce4+ sites. Raman spectra showed a redshift of F2g mode that caused by the Fe doping. The samples of both undoped CeO2 and Fe-doped CeO2 exhibited room temperature ferromagnetism, and the saturated magnetization (M s ) increased with increasing Fe content until x = 0.05, and then the samples displayed ferromagnetic loops as well as paramagnetic behavior. The roles of Ce3+ and Fe3+ spin electrons are discussed for the ferromagnetism in the Fe-doped CeO2.